2017
DOI: 10.1039/c7dt00104e
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the local environment around metal ions: a solution chemical and structural study of some multidentate tripodal ligands

Abstract: Manganese(II), copper(II) and zinc(II) complexes of four polydentate tripodal ligands (tachpyr (N,N',N''-tris (2-pyridylmethyl)-cis,cis-1,3,5-triaminocyclohexane), trenpyr (tris[2-(2-pyridylmethyl)aminoethyl]amine, tach3pyr (N,N',N''-tris(3-pyridylmethyl)-cis,cis-1,3,5-triaminocyclohexane) and tren3pyr (tris[2-(2-pyridylmethyl)aminoethyl]amine)) were characterized in both solution and solid states. A combined evaluation of potentiometric, UV-VIS, NMR and EPR data allowed the conclusion of both thermodynamic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Accordingly, tripodal ligands are applied in diverse fields of chemistry, such as metal sensing, 1 metalloenzyme modelling, [2][3][4][5][6][7] and stabilization of reactive species and intermediates 8,9 and even for the development of molecular motors. 10 Some tripodal ligands and/or their metal complexes show high tendency to selfassembly, creating metal-organic frameworks, 11 metallocages with colorful compositions, 12 hydrogels 13 or other mesophase structures, 14 thus expanding their application to supramolecular chemistry as well. The advantages of peptide-type tripodal ligands in coordination chemistry have been recognized in the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, tripodal ligands are applied in diverse fields of chemistry, such as metal sensing, 1 metalloenzyme modelling, [2][3][4][5][6][7] and stabilization of reactive species and intermediates 8,9 and even for the development of molecular motors. 10 Some tripodal ligands and/or their metal complexes show high tendency to selfassembly, creating metal-organic frameworks, 11 metallocages with colorful compositions, 12 hydrogels 13 or other mesophase structures, 14 thus expanding their application to supramolecular chemistry as well. The advantages of peptide-type tripodal ligands in coordination chemistry have been recognized in the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the extension in space, they can be one, two or three-dimensional. Several key factors control self-assembly of CPs like the coordination environment of the metal ion, 25,26 ligand functionality, 27 ligand flexibility, [28][29][30] metal to ligand ratio, 31,32 temperature, 33,34 pH, 35 solvent, [36][37][38] anions [39][40][41][42][43] and non-covalent interactions. [44][45][46][47][48][49] Among these factors, anions are one of the most important to be noted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, desferrioxamine (DFO), a first line agent of the treatment of an iron overload, was utilized in clinical trials for the treatment of hepatocellular carcinoma (Scheme ). It has also been reported that copper chelators induce the cell death in colon cancer cells via the generation of reactive oxygen species. Tripodal ligands such as N , N′ , N ″-tris­(2-pyridylmethyl)- cis , cis -1,3,5-triaminocyclohexane (tachpyr) provide additional donor sites and affect the steric environment around the metal center allowing more efficient metal chelating, resulting in the activation of intracellular cell death mechanisms. However, care needs to be exercised in the use of metal chelators, because of the side effects possibly due to the nonspecific complexation with intracellular metal cations.…”
Section: Introductionmentioning
confidence: 99%